3D modeling of radiation conditions and dose rates for personnel during dismantling of the roof structures of the Shelter object - Pashynov, M.; Pidbereznyy, S.; Paskevych, S. (Вопросы атомной науки и техники, 2020)
The results of three-dimensional modeling of personnel work conditions in radiation-hazardous conditions of the “Shelter” object, carried out using the software complex HVRC VRdose, are presented. Estimations of dosing loads on personnel during the dismantling of a metal farm on the roof of the “Shelter” object are carried out. The obtained simulation data showed good convergence with the data obtained during the development of a working design for dismantling of this construction. Представлені результати тривимірного моделювання умов роботи персонала у радіаційно небезпечних умовах об’єкта «Укриття», виконаного з допомогою програмного комплекса HVRC VRdose. Оцінені дозові навантаження на персонал при виконанні рабіт по демонтажу металевої ферми на покрівлі об’єкта «Укриття». Отримані дані моделювання показали добру узгодженість з даними, які були отримані при розробці робочого проекта демонтажу цієї конструкції. Представлены результаты виртуального моделирования условий работы персонала в радиационно опасных условиях объекта «Укрытие», выполненного с помощью программного комплекса HVRC VRdose. Оценены дозовые нагрузки на персонал при выполнении работ по демонтажу металлической фермы на кровле объекта «Укрытие». Полученные данные моделирования показали хорошую сходимость с данными, которые были получены при разработке рабочего проекта демонтажа этой конструкции.